2017
DOI: 10.1037/ser0000157
|View full text |Cite
|
Sign up to set email alerts
|

The role of personality traits and barriers to mental health treatment seeking among college students.

Abstract: Many college students experience a mental health problem yet do not seek treatment from a mental health professional. In the present study, we examined how perceived barriers (stigma perceptions, negative attitudes about treatment, and perceptions of practical barriers), as well as the Big Five personality traits, relate to treatment seeking among college students reporting a current mental health problem. The sample consisted of 261 college students, 115 of which reported experiencing a current problem. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…A relationship between stigma and attitudes toward help seeking has been identified. College students who report higher levels of public stigma are less likely to seek mental health services (Wu et al, ), and perceived stigma and self‐stigma are associated with a lower likelihood that students with a mental health concern will seek treatment (Jennings et al, ). Vogel, Wade, and Hackler () determined that perceived public stigma was positively related to self‐stigma, that self‐stigma was negatively related to counseling attitudes, and that counseling attitudes were positively related with a willingness to seek help.…”
Section: Perceived Public Stigma and Self‐stigma Toward Help Seekingmentioning
confidence: 99%
“…A relationship between stigma and attitudes toward help seeking has been identified. College students who report higher levels of public stigma are less likely to seek mental health services (Wu et al, ), and perceived stigma and self‐stigma are associated with a lower likelihood that students with a mental health concern will seek treatment (Jennings et al, ). Vogel, Wade, and Hackler () determined that perceived public stigma was positively related to self‐stigma, that self‐stigma was negatively related to counseling attitudes, and that counseling attitudes were positively related with a willingness to seek help.…”
Section: Perceived Public Stigma and Self‐stigma Toward Help Seekingmentioning
confidence: 99%
“…Research indicates that the most important barriers to seeking mental health therapy among young adults include perceived stigma, self-denial of a mental health problem, negative attitudes about treatment, and practical barriers, such as not knowing where to seek help, cost issues, etc. [4,5]. These findings prompt universities and institutions providing undergraduate and post-graduate education and training to ensure that stress management programs are always available and, importantly, that these services are structured in such a way as to engage young people.…”
Section: Introductionmentioning
confidence: 99%
“…Under normal conditions, undergraduate students witness several important changes related to personal life and education. University students might feel homesick and overwhelmed by academic demands, which might become a major cause of stress for undergraduate students [ 5 , 6 ]. During this transition, students might also experience minor psychological problems related to sleep, eating habits, and concentration [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may also be the case that in relation to stigma, a greater focus on self‐stigma, rather than public stigma as was the focus of assessment in the present study, may have revealed different outcomes. In support of this, some (Jennings et al, ; Wade et al, ), but not all (Conner et al, ; Jennings et al, ) studies in other fields have shown that self‐stigma is more strongly related to treatment‐seeking for mental health problems than concern about stigmatizing reactions from others.…”
Section: Discussionmentioning
confidence: 95%